206 Emergency department clinical leads' experiences of implementing primary care services where GPs work in or alongside emergency departments in the UK: a qualitative study. Issue 12 (23rd November 2020) - Edwards, Michelle; Cooper, Alison; Davies, Freya; Carson-Stevens, Andrew; Hughes, Thomas; Porter, Alison; Snooks, Helen; Edwards, Adrian
Abstract : Aims/Objectives/Background: We aim to describe ED clinical leads' experiences of implementing and delivering 'primary care services' and 'emergency medicine services' where GPs were integrated into the ED team. NHS England policy has promoted services in which patients presenting to EDs with non-urgent problems are directed to general practitioners (GPs) and other primary care clinicians working within or alongside EDs to address increasing demand. Our findings describe variation in the ways that these primary care services are implemented and the ways in which GPs work within them. We also highlight successes and challenges in implementing such services. Methods/Design: We conducted interviews with ED clinical leads in England (n=19) and Wales (n=2). We used framework analysis to analyse interview transcripts and explore differences across 'primary care services', 'emergency medicine services' and emergency departments without primary care services. Results/Conclusions: In EDs with separate primary care services, success was reported with a distinct workforce of primary care clinicians, who improved waiting times and flow by seeing primary care-type patients in a timely way, using fewer investigations, and enabling ED doctors to focus on more acutely unwell patients. Some challenges were: aligning services with the policy guidance, inconsistent demand for primary care, accessible community primary care services, difficulties recruiting GPs, lack of funding, difficulties agreeing governance protocols and establishing effective streaming pathways. Where GPs were integrated into an ED workforce success was reported as managing the demand for both emergency and primary care and reducing admissions. To support successful and sustainable primary care services in or alongside EDs, policy makers and commissioners should consider varied ways that GPs can be employed to manage local demand and also local contextual factors such as the ability to recruit and retain GPs, sustainable funding, clear governance frameworks, training, support and guidance for all staff.